PENERAPAN MODEL PEMBELAJARA LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SDN 165 PEKANBARU - Marhadi, Hendri; ', Muhairah; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This study was not optimal background science student learning outcomes, of the 37 students there are 22 students (59.5%) who have not yet reached KKM. The research problems are " Is Direct Application of Learning Model Can Improve Results grade science students learn VB SDN 165 Pekanbaru” ?. The aim of research using PTK is to improve student learning outcomes. Results of the study, the activity of teachers at the first meeting of the first cycle of 65% at the second meeting increased to 75%. At the third meeting of the second cycle is the 80% increase to 95%. Activity of students in the first cycle dipertemuan first 70% to the second meeting increased to 75%. The third meeting of the second cycle increased from 85% to 95% meeting to four. Improving student learning outcomes of basic scores with an average value of 66.21, then increased in the first cycle with an average value of 76.90, an increase in the results of this study amounted to 16.14%. The average score of 66.21 basis increased to 81.22 with an increase of 22.67%. Individual mastery of basic scores were originally 22 people increased in the first cycle of 29 people and the second cycle increased to 32 people. Classical completeness on the basis of the percentage score of 59.45% with incomplete category, the second cycle of 78.38% with a category is not exhaustive, and the second cycle increased to 86.49% with a complete category. Based on research that has been done, the application of direct learning model can improve learning achievement grade science students VB SDN 165 Pekanbaru.Keywords : Direct Learning Model , the result of learning sains , PTK